2015
DOI: 10.1371/journal.pone.0134919
|View full text |Cite
|
Sign up to set email alerts
|

A Cone-Beam Computed Tomographic Study on Mandibular First Molars in a Chinese Subpopulation

Abstract: The purpose of this study was to conduct a cone-beam computed tomographic (CBCT) investigation on the root and canal configuration of the mandibular first molars, especially the morphology of the disto-lingual (DL) root, in a Chinese subpopulation. A total of 910 CBCT images of the mandibular first molars were collected from 455 patients who underwent CBCT examinations as a preoperative assessment for implants or orthodontic treatment. The following information was analyzed and evaluated: tooth position, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 32 publications
(40 reference statements)
6
40
4
Order By: Relevance
“…As for the mandibular first molar mesial root, both ethnic groups presented a low prevalence of Vertucci type I morphologies, which is in line with the previous literature (49,50). The most common Vertucci types for this root are Vertucci type II for whites (46.9% in the white group and 12.3% in the Asian group) and type IV for Asians (76.8% in the Asian group and 41.9% in the white group).…”
Section: Clinical Researchsupporting
confidence: 88%
See 1 more Smart Citation
“…As for the mandibular first molar mesial root, both ethnic groups presented a low prevalence of Vertucci type I morphologies, which is in line with the previous literature (49,50). The most common Vertucci types for this root are Vertucci type II for whites (46.9% in the white group and 12.3% in the Asian group) and type IV for Asians (76.8% in the Asian group and 41.9% in the white group).…”
Section: Clinical Researchsupporting
confidence: 88%
“…Two Chinese studies reported a type IV prevalence in 87.7% (50) and 93.9% (51) of cases, whereas several predominantly white countries presented a lower prevalence, including Belgium (6) (16.4%), Spain (11) (37.8%), Brazil (52) (40.4%), and Italy (45) (62.4%). The same evidence is available for Vertucci type II results because Chinese studies show a prevalence of 1.7% (51) and 5.6% (50), whereas in predominantly white countries the prevalence of these morphologies was 5.0% in Belgium (6), 27.4% in Italy (45), 38.6% in Brazil (52), and 51.3% in Spain (11). The findings mentioned for the mesial root of mandibular first molars can be extended to second molars and are in agreement with the current literature (9,11,45,52).…”
Section: Clinical Researchmentioning
confidence: 91%
“…The included studies (n = 25) reported data on 25 445 teeth from 13 142 patients including 2540 maxillary first molars, 3300 maxillary second molars, 5240 mandibular first molars, 11 308 mandibular second molars, 1656 mandibular first premolars and 1401 mandibular second premolars. Evaluation included at least 4110 males and 5559 females, once six studies reported incomplete data regarding gender ratio (Yu et al 2012, Zhang et al 2015, Rogazkyn et al 2016, Pawar et al 2017, von Zuben et al 2017, Pedemonte et al 2018. The average age of the patients was 42.3 years and was calculated based on 18 studies that reported this information.…”
Section: Resultsmentioning
confidence: 99%
“…The mesial root has two separated canals in about 90% of cases (type IV), and in 10 % the two canals are joined into one canal at the apex (type II), while the distal root usually contains one straight oval canal (type I) (Figure 16). The incidence of C-shaped root canal is low in this tooth and about 2% [60] ( Table 5 shows the root canal configurations for mandibular first molar in recent studies [30,33,[51][52][53][54][55][56][57][58][59]).…”
Section: Root Canal Morphology Of Mandibular Molars 41 Mandibular Fimentioning
confidence: 99%